Clinical features of depression in Asia: Results of a large prospective, cross‐sectional study - Srisurapanont, Manit; Hong, Jin Pyo; Si, Tian-mei; Sulaiman, Ahmad Hatim; Liu, Chia Yih; Udomratn, Pichet; Bae, Jae Nam; Fang, Yiru; Chua, Hong Choon; Liu, Shen-Ing; George, Tom; Bautista, Dianne; et al. (Wiley, 2013)
Introduction: The objective of this study was to investigate the clinical features of depression in Asian patients. Methods: It was a cross-sectional, observational study of depression in China, Korea, Malaysia, Singapore, Taiwan, and Thailand. Participants were drug-free outpatients with depressed mood and/or anhedonia. Symptoms and clinical features were assessed using the Montgomery–Asberg Depression Rating Scale, Symptoms Checklist 90-Revised (SCL-90-R), and the Fatigue Severity Scale. Other measures included the Medical Outcome Survey 36-Item Short-Form Health Survey (SF-36), the Sheehan Disability Scale,and the Multidimensional Scale of Perceived Social Support (MSPSS). Results: A total of 547 outpatients with major depressive disorder were included in the analyses. Among the Montgomery–Asberg Depression Rating Scale symptoms, “reported sadness” and “reduced sleep” had the highest severity, with means (SDs) of 3.4 (1.2) and 3.4 (1.6), respectively.Apart from the SCL-90-R depression and anxiety domains, the SCL-90-R obsession–compulsion syndrome had the highest domain score, with a mean (SD) of 1.9 (0.9). Among eight domains, the mean (SD) SF-36 pain subscale score of 58.4 (27.7) was only second to that for the SF-36 physical function. In comparison to other disability domains, the Sheehan Disability Scale work/school had the highest subscale score, with a mean (SD) of 6.5 (2.9). The mean (SD) MSPSS “family” subscale score of 4.7 (1.7) was higher than the MSPSS “friends” and “significant others” subscale scores. Discussion: This study suggests that pain has a minimal impact on the quality of life in Asian patients with depression. Noteworthy issues in this population may include insomnia, obsessive–compulsive symptoms, working/school disability, and family support.